2009
DOI: 10.1088/1674-1056/18/1/051
|View full text |Cite
|
Sign up to set email alerts
|

A new analytical model of high voltage silicon on insulator (SOI) thin film devices

Abstract: A new analytical model of high voltage silicon on insulator (SOI) thin film devices is proposed, and a formula of silicon critical electric field is derived as a function of silicon film thickness by solving a 2D Poisson equation from an effective ionization rate, with a threshold energy taken into account for electron multiplying. Unlike a conventional silicon critical electric field that is constant and independent of silicon film thickness, the proposed silicon critical electric field increases sharply with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Wang et al [13] used a needle-plate reactor discharge to treat acid orange wastewater and showed that the degradation efficiency enhanced with increasing peak voltage and discharge frequency. Dong et al [14] used a multineedle-plate discharge reactor to treat formaldehyde and optimized the reactor to achieve an optimum degradation efficiency. Sun et al [15] used a gas-phase multi-needle-plate discharge system to degrade the organic pollutant methyl orange.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [13] used a needle-plate reactor discharge to treat acid orange wastewater and showed that the degradation efficiency enhanced with increasing peak voltage and discharge frequency. Dong et al [14] used a multineedle-plate discharge reactor to treat formaldehyde and optimized the reactor to achieve an optimum degradation efficiency. Sun et al [15] used a gas-phase multi-needle-plate discharge system to degrade the organic pollutant methyl orange.…”
Section: Introductionmentioning
confidence: 99%
“…Power MOS devices have many advantages, such as high input impedance, positive temperature coefficient of onresistance, high switching frequency and wide safe working area. However, an important question with regard to LD-MOS is the disadvantage of "silicon limit" R on,sp ∝ BV 2.5 , which exists between specific on-resistance and breakdown voltage [1][2][3] . In order to break the "silicon limit", domestic and foreign scholars have proposed super-junction structure, high-k technology, and field plate technology to reduce the on-resistance and retain a high blocking voltage [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%